Conceptualizing and Measuring Immigration Policies: A Comparative Perspective. Issue 3 (22nd May 2014) - Bjerre, Liv; Helbling, Marc; Römer, Friederike; Zobel, Malisa
<x xml:space="preserve">Abstract</x> In the last decade, researchers have developed many innovative ideas for the construction of indices measuring immigration policies. Methodological considerations have, however, been largely absent from the discussion. To close this gap, this paper investigates the characteristics of existing indices by critically comparing and discussing them. We start by providing a definition of immigration policy which may serve as a benchmark when assessing the indices. By means of the analytical framework developed by Munck and Verkuilen (2002), which we adapt and customize for our analysis, we then evaluate the conceptualization, measurement, and aggregation, as well as the empirical scope of thirteen immigration policy indices. We discuss methodological strengths and weaknesses of the indices, how these affect the research questions that can be answered and what the next steps in index building within the field of immigration policy should be.